Strategi Layanan Kesehatan Reproduksi pada Remaja: Literature Review - Katrina Auri; Elizabet Catherine Jusuf; Mardiana Ahmad (Faletehan Health Journal, 2022)
Adolescents are the most important targets in reproductive health programs. The typical nature of teenagers is to have great curiosity, love adventure, like challenges and dare to take risks for their actions without careful consideration, and inappropriate decision making in facing problems. Therefore, they might potentially fall into risky behaviors that cause short and long term impacts in physical and psychological health problems. The purpose of the study was to know reproductive health service strategies in adolescents. The research used literature studies. To search the articles, PubMed database and Google Scholar publication year from 2015 to 2021 were used. There were 18 relevant articles based on inclusion criteria. Reproductive health service strategies in adolescents could be done through mass media such as televition, radio, leaflets and pocketbook giving. Mobile phones were also able to be utilized by providing applications and social media services. The strategies can provide better benefits because they are able to increase adolescent knowledge and most importantly to keep adolescents secret.